The Effect of Educational, Esthetic, and Escapist on Revisit Intention: The Mediating Role of Emotional Engagement Tourists at the Bandung Geological Museum - Shantia Nur Fadilah; Yadi Ernawadi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of educational, aesthetic, escapist, tour guide performance, and scentscape on revisit intention through emotional engagement in tourists of the Bandung City Geological Museum. This study uses a quantitative approach with a survey method involving 146 respondents. Data analysis using structural equation modeling with the help of SmartPLS version 3.0. The results of the study show that educational, aesthetic, and escapist have a positive effect on revisit intention through emotional engagement. This finding is expected to help the management of the Geological Museum in prioritizing the development of programs that are able to create escapists, followed by strengthening educational and aesthetic aspects, in order to increase tourist revisit intention. Further research is suggested to develop this study using theoretical foundations and other mediating variables to explain the psychological mechanisms that link the travel experience with revisit intention.